Exploring the mechanism of Taohong Siwu Decoction on the treatment of blood deficiency and blood stasis syndrome by gut microbiota combined with metabolomics - Yao He; Huajuan Jiang; Kequn Du; Shengju Wang; Minmin Li; Chuan Ma; Fang Liu; Yan Dong; Chaomei Fu (BMC, 2023)
Abstract Background Taohong Siwu Decoction (THSWD) is a prescription which included in the "List of Ancient Classic Prescriptions (First Batch)" issued by the National Administration of Traditional Chinese Medicine (TCM) and the National Medical Products Administration of the People's Republic of China. THSWD is effective and widely applied clinically for many diseases caused by blood deficiency and stasis syndrome in TCM, such as primary dysmenorrhea, menopausal syndrome, coronary heart disease, angina pectoris, and diabetes. Methods The TCM model of blood deficiency and blood stasis syndrome was prepared by ice water bath combined with cyclophosphamide, and the rats were randomly divided into control group, blood deficiency, and blood stasis model group, positive group, and THSWD treatment group. Pharmacodynamics measured the blood routine, blood coagulation, and other related indexes in rats. UHPLC-MS technology was used to analyze the changes in the fingerprints of metabolites in the plasma of rats with blood deficiency and blood stasis syndrome, and combined with mass spectrometry information and public database retrieval, to find potential biomarkers for screening metabolites. At the same time, 16S rDNA sequencing technology was used to identify intestinal flora, and statistical analysis was used to find differences in strain diversity between groups. Results THSWD administration can significantly improve the physical signs, blood routine, and hematopoietic factors caused by the blood deficiency and blood stasis syndrome model, and improve the symptoms of blood deficiency. The results of the general pharmacological studies showed THSWD groups improved changes in blood plasma viscosity and coagulation-related factors caused by modeling, and improved coagulation function significantly. The metabolomic analysis found that compared to the model group, THSWD exerted better effects on β-alanine, taurine, l-tyrosine, l-arginine, Eugenol, sodium deoxycholate, and deethylatrazine. Twenty-three potential differential metabolites showed intervention effects, mainly involved in eight metabolic pathways, including amino acid metabolism, taurine and hypotaurine metabolism, vitamin metabolism, and nucleotide metabolism. Gut microbiota data showed that, compared to the control group, the relative abundance and value of Firmicutes and Bacteroidota of the blood deficiency and blood stasis model group was significantly reduced, while the relative abundance of Actinobacteria, Spirochaetota, Proteobacteria, Campilobacterota, and other pathogenic bacteria was significantly increased. Following THSWD intervention, the abundance of beneficial bacteria increased, and the abundance of pathogenic bacteria decreased. Correlation analysis between the gut microbiota and differential metabolites showed that the two are closely related. THSWD affected the host blood system through mutual adjustment of these two factors, and improved blood deficiency and blood stasis syndrome in rats. Conclusion The blood deficiency and blood stasis syndrome model of TCM disease caused by ice bath combined with cyclophosphamide lead to changes in the pharmacology, metabolomics, and gut microbiota. The intervention of THSWD can improve the symptoms caused by blood deficiency and blood stasis. The mechanism is mainly through the regulation of platelet function and amino acid metabolism.